Effectiveness of an algorithm‐based care pathway for patients with non‐valvular atrial fibrillation presenting to the emergency department. Issue 1 (18th February 2022) - Masica, Andrew; Brown, Rachel; Farzad, Ali; Garrett, John S.; Wheelan, Kevin; Nguyen, Hoa L.; Ogola, Gerald O.; Kudyakov, Rustam; McDonald, Brandy; Boyd, Bethany; Patel, Avani; Delaughter, Craig
Abstract: Objective: Atrial fibrillation (AF) carries substantial morbidity and mortality. Evidence‐based guidelines have been synthesized into emergency department (ED) AF care pathways, but the effectiveness and scalability of such approaches are not well established. We thus evaluated the impacts of an algorithmic care pathway for ED management of non‐valvular AF (EDAFMP) on hospital use and care process measures. Methods: We deployed a voluntary‐use EDAFMP in 4 EDs (1 tertiary hospital, 1 cardiac hospital, 2 community hospitals) of an integrated delivery organization using a multifaceted implementation approach. We compared outcomes between patients with AF treated using the EDAFMP and historical and contemporaneous "usual care" controls, using a propensity‐score adjusted generalized estimating equation. Patients with an index ED encounter for a primary visit reason of non‐valvular AF (and no excluding concurrent diagnoses) were eligible for inclusion. Results: Preimplementation (January 1, 2016–December 31, 2016), 628 AF patients were eligible; postimplementation (September 1, 2017–June 30, 2019), 1296, including 271 (20.9%) treated with the EDAFMP, were eligible. EDAFMP patients were less likely to be admitted than both historical (adjusted odds ratio [aOR], 95% confidence interval [CI]: 0.45, 0.29–0.71) and contemporaneous controls (aOR, 95%CI: 0.63, 0.46–0.86). ED visits and hospital readmissions over 90 days subsequent to index ED encounters were similar between postimplementation EDAFMP and usual care groups. EDAFMP patients were more likely to be prescribed anticoagulation (38% v. 5%, P < 0.001) and be referred to a cardiologist (93% vs 29%, P < 0.001) versus the comparator group. Conclusion: EDAFMP use is associated with decreased hospital admission during an index ED encounter for non‐valvular AF, and improved delivery of AF care processes.